Bridging to transplant and post-transplant maintenance therapy with FLT3 inhibitors in patients with relapsed or refractory FLT3 mutated acute myeloid leukemia - Hirose, Natsuki; Tachibana, Takayoshi; Izumi, Akihiko; Sato, Shuku; Tadera, Noriyuki; Tamai, Yotaro; Kanamori, Heiwa; Tanaka, Masatsugu; Nakajima, Hideaki (Hematology (Luxembourg), 2023)
This single-center retrospective study was performed to evaluate the safety and efficacy of FMS-like tyrosine kinase 3 (FLT3) inhibitors before and after allogeneic hematopoietic cell transplantation (HCT) in relapsed/refractory patients with FLT3-mutation positive acute myeloid leukemia (AML). Ten patients who met the eligibility criteria were included. Eight of them achieved hematological remission at HCT, within a median span of 79 days (range: 43-197). In post-HCT, patients started maintenance therapy (MT; median time-to-start 79 days, range: 43-197), and the median duration of MT was 390 days (range: 67-815). Grade 3 hematological adverse events (AEs) were found in two patients, and non-hematological AEs were found in five patients. Nine patients underwent either dose reduction, discontinuation of therapy, or a switch to another FLT3 inhibitor due to AEs. Disease relapse occurred in one patient during MT. At the time of the last follow-up, seven patients are alive and disease-free, while three have died due to infection or transplant complications. In relapsed/refractory FLT3 mutation-positive AML, the use of FLT3 inhibitors can lead to high response rates and provide a safe bridge from HCT to MT. If sufficient attention is paid to safety, this therapy is expected to prevent disease relapse even with reduced dosages.